Feeling vibrations from a hearing and dual-sensory impaired perspective - Russ Palmer; Olav Skille; Riitta Lahtinen; Stina Ojala (International Association for Music & Medicine, 2022)
Working with hearing and dual-sensory impaired clients presents challenges for music therapy professionals. Feeling and experiencing the vibrations produced by music help to understand what the concept of music is. Music and vibroacoustic therapies have overlapping effects. Music is for listening while vibroacoustic therapy is mainly similar to physiotherapy. Where vibroacoustic (VA) facilities are not available, some flexible methods could be adapted. One can use a music centre with two separate, moveable speakers positioned on a wooden floor to enhance music vibrations. In conjunction inflatable balloons can be manipulated by the clients. Balloons can be held towards the sound source and used to test the variations of the intensity and dynamics of the vibrations in the room. The choice of music styles plays an important role to amplify the vibrations and introduce music to the clients. Clients’ feedback was very positive indicating they were able to feel some musical tones from low, middle and high levels. These methods appeared to enhance musical vibrations and give some therapeutic experiences, i.e. relaxation and awareness of musical tones. This approach has been tested over 25 years and the individual feedback supports notions on how tones are felt through the body.